CRISPR/Cas-mediated mRNA knockdown in the embryos of Xenopus tropicalis - Xiao-Lin Lin; Yi-Min Zhou; Ke Meng; Jia-Yi Yang; Han Zhang; Jin-Hua Lin; Hai-Yan Wu; Xiao-Yu Wang; Hui Zhao; Shan-Shan Feng; Kyu-Sang Park; Dong-Qing Cai; et al. (Cell & Bioscience)
Abstract The Xenopus tropicalis (Western clawed frog) is an important amphibian model for genetics, developmental and regenerative biology, due to its diploid genetic background and short generation time. CRISPR-Cas13 and CRISPR interference (CRISPRi) systems have recently been employed to suppress mRNA expression in many organisms such as yeast, plants, and mammalian cells. However, no systematic study of these two systems has been carried out in Xenopus tropicalis. Here, we show that CRISPRi rather than CRISPR-Cas13 is an effective and suitable approach to suppress specific mRNA transcription in Xenopus tropicalis embryos. We demonstrated that CRISPRi composed of dCas9 and KRAB-MeCP2 (dCas9-KM) can efficiently target exogenous and endogenous transcripts in Xenopus tropicalis embryos. Moreover, our data suggest that the new KRAB domain from ZIM3 protein (ZIM3-KRAB, ZIM3K) alone has a comparable transcript targeting capacity in Xenopus tropicalis embryos to the traditional fusion repressor KRAB-MeCP2 in which the KRAB domain from KOX1 protein. In conclusion, our results demonstrate that CRISPRi rather than CRISPR-Cas13 is an efficient knockdown platform to explore specific gene function in Xenopus tropicalis embryos.